WHETHER THE DEVELOPMENT OF ELECTROMOBILITY POSITIVELY INFLUENCES THE QUALITY OF TRANSPORT SERVICES IN CITIES - CRITICAL ANALYSIS - Bielski, Bartłomiej; Bednarczyk, Maciej (Acta Universitatis Nicolai Copernici. Zarządzanie, 2020)
Interest in electromobility among the public has been growing over the last years. In order to determine the impact of the development of electric cars on the quality of urban transport services, factors that may affect the transport of passengers and cargo and related facilities or disadvantages should be analysed. The article presents electromobility characteristics and analyses of conditions related to this modernization. The shortcomings and risks of what is often referred to as the technology of the future - electromobility - are also presented.